(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Freedom is a constituent of what we call God’s “image” in human beings. It represents the effect of their good choice, the use of the gift of free will, received from the merciful God, for salvation. Human dignity is fundamental to human beings. It represents God’s gift as an inalienable right from the Creator. Human dignity is also a call from their Creator: those in Christ acquire the values of spiritual and intellectual discernment, of spiritual courage, and they oppose”—in complete autonomy from God— the great virtue of Christian responsibility, the interface of human dignity, to the ideological use of human “rights”.